Origin, Synthesis and Various Mechanisms of Hypericin as Antidepressant, Photosensitizer and Antiviral: Hypericin as Antidepressant, Photosensitizer and Antiviral - Ahsan Waqar, Muhammad; Riaz, Tehseen; Zaman, Muhammad; Majeed, Imtiaz; Nadeem Alvi, Muhammad; Ishaque, Ambreen; Tabassam, Naila; Mehboob, Tooba; Waqas, Muhammad; Munir, Minahal; Tayyab, Saqiba (Pakistan Journal of Health Sciences, 2022)
Large number of hypericum species have been found around the globe. One of which is the Hypericin, that is extracted from the Hypericum perforatum. This review focuses on the brief history of the hypericin, its various natural and semisynthetic sources, the precise pharmacokinetics of the hypericin as well as describes the detailed actions of hypericin as an antidepressant, antiviral and as a phytotoxic agent. In chemical synthesis, Emodin had been found to be the ultimate likely hypericin precursor. Hypericin is not a newly discovered agent to the community of research, nonetheless it has been accomplishing an innovative and a promising position as a very effective agent in the medical diagnostics as well as in the therapeutic applications. Hypericin had been investigated as a good candidate for the treatment of depression, cancer and also had an efficacy against various viral agents as well. Depression is treated by voltage dependent Ca2+ influx reduction. Photosensitizing property is due to hemoglobin absorption. Antiviral activity is through the deactivation of enveloped viruses in life cycle of virus. With relatively fewer side effects this agent can be utilized as an alternate of various semisynthetic medications.